Narrative-based psychotherapies for mood disorders: A scoping review of the literature - Lisa D. Hawke; Anh T.P. Nguyen; Terri Rodak; Philip T. Yanos; David J. Castle (Elsevier, 2023)
Background: Narrative-based psychotherapies are strengths-based psychotherapeutic approaches that could be beneficial for people with mood disorders. This scoping review synthesizes the research on the outcomes of various modalities of narrative-based psychotherapies for adults with mood disorders. Methods: Scoping review methodology was followed. Relevant studies were identified via systematic database searches. Articles were eligible if they reported on the outcomes of narrative therapy, narrative therapy integrated with other treatment modalities, and other narrative-based psychotherapies delivered to adults with mood disorders, and were published in English or French. Eighteen reports were included in the review. Results: A small body of research has applied the original narrative therapy model, integrated narrative therapies, and other narrative-based psychotherapies to depressive disorders and, to a lesser extent, to bipolar disorder. Across studies and methodologies, these approaches are associated with improvements in mood symptoms and other metrics. Comparative research tentatively suggests that outcomes of narrative approaches may be similar to those of other psychotherapeutic approaches, across a range of populations. Conclusions: Narrative approaches to psychotherapy may constitute promising psychotherapeutic modalities for adults with mood disorders. However, these approaches are under-researched to date; ongoing research is justified to establish a more robust evidence base on the efficacy and effectiveness of narrative-based psychotherapies for mood disorders.